2015
DOI: 10.1111/dmcn.12814
|View full text |Cite
|
Sign up to set email alerts
|

Motor performance and correlates of mental health in children who are deaf or hard of hearing

Abstract: SDQStrengths and Difficulties Questionnaire ZNA Z€ urich Neuromotor Assessment AIM This cross-sectional study investigates the relationship between motor performance and mental health in a representative population of children with hearing impairment.METHOD Ninety-three pupils (45 males, 48 females) aged 6 years to 16 years (mean 11y 3mo, SD 2y 9mo) with hearing impairment of at least 40dB and a Nonverbal IQ greater than 70 were assessed for motor performance with the Z€ urich Neuromotor Assessment (ZNA) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
1
21
0
3
Order By: Relevance
“…Fellinger pointed this out by asking the question: ''What kind of evidence-based interventions need to follow UNHS in order to support families to actively foster the development of a strong identity and positive mental health of their child with PCHI, beyond the drive for 'normalization'?'' [47]. This question calls for longitudinal research designs with a detailed follow-up of DHH children in order to study treatment effects and causality.…”
Section: Discussionmentioning
confidence: 99%
“…Fellinger pointed this out by asking the question: ''What kind of evidence-based interventions need to follow UNHS in order to support families to actively foster the development of a strong identity and positive mental health of their child with PCHI, beyond the drive for 'normalization'?'' [47]. This question calls for longitudinal research designs with a detailed follow-up of DHH children in order to study treatment effects and causality.…”
Section: Discussionmentioning
confidence: 99%
“…HI children typically have lower scores on psychomotor scales than normal hearing (NH) children [2,8]. For instance, more than the 30% of HI children showed retardation in the acquisition of head control or independent gait [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, more than the 30% of HI children showed retardation in the acquisition of head control or independent gait [9]. Poor motor performance does not appear to affect self-efficacy in HI children [10], but it has been related to language deficiencies, poorer symbolic play, emotion dysregulation and social difficulties in interacting with other children [8,11]. Children with cochlear implanta show a drop in their gross motor performance coinciding with surgery, and a period of at least two years is needed to recover the developmental delay [12].…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6] This data 2-6 suggest that apart from the type and severity of the motor disability, a neuromotor intervention program for children with CP may be influenced by the child's age and level of cognition as well as sociodemographic factors (e.g. type of insurance, parental education).…”
Section: 2mentioning
confidence: 99%
“…2 Recent research on motor development in hearing children has found that children with coordination problems, such as developmental coordination disorder (DCD), are at increased risk of a range of physical and mental health problems, including internalizing problems, such as anxiety and depression. 3 There has been little research, if any, on the possible associations between motor skills and mental health in children and adolescents who are deaf or partial hearing, and so the article by Fellinger et al 4 is very timely. They found that 57% of children and adolescents (aged 6-16y) with hearing impairment in their sample had significant motor difficulties (scoring in the bottom 5% of a standardized assessment), suggesting high levels of comorbid DCD.…”
mentioning
confidence: 99%